Resource Wealth and Happiness: Evaluating The 'Resource Curse' VS. 'Resource-Based Development' Theories - Muhammad Ichsan Fadillah (Return : Study of Management, Economic and Bussines, 2025)
The wealth of natural resources in different countries has a complex impact on economic development and people's welfare. The aim of this research is to critically evaluate the influence of natural resource wealth on happiness, assess the effectiveness of governance and policy in mediating this relationship, and provide actionable recommendations for policymakers to optimize the benefits of resource extraction. The analysis was conducted using data from 116 countries over the period 2017-2022. Linear regression models were used to examine the effect of mining production and national GDP on happiness. Data was taken from World Mining Data, the World Bank, and the World Happiness Report. The model used includes two approaches: one that measures the effect of national GDP on happiness, and another that considers the interaction between national GDP and mining production. Results show that national GDP has a significant positive correlation with happiness, supporting the “resource-based development” theory. However, the interaction between national GDP and mining production shows a negative effect, reflecting aspects of the “resource curse” theory. Variability in the impact of mining production was also observed, suggesting that the social and economic context influences this relationship. This research highlights the importance of effective natural resource management to improve people's happiness. While resource wealth can support economic growth, over-reliance on resource spending can reduce its positive impact. The findings provide insights for policymakers to formulate balanced strategies to utilize natural resources for sustainable social welfare.